Differential regulation of lineage-determining transcription factor expression in innate lymphoid cell and adaptive T helper cell subsets - Fang, Difeng; Healy, Ayanna; Zhu, Jinfang (Frontiers in Immunology, 2023)
CD4 T helper (Th) cell subsets, including Th1, Th2 and Th17 cells, and their innate counterparts innate lymphoid cell (ILC) subsets consisting of ILC1s, ILC2s and ILC3s, display similar effector cytokine-producing capabilities during pro-inflammatory immune responses. These lymphoid cell subsets utilize the same set of lineage-determining transcription factors (LDTFs) for their differentiation, development and functions. The distinct ontogeny and developmental niches between Th cells and ILCs indicate that they may adopt different external signals for the induction of LDTF during lineage commitment. Increasing evidence demonstrates that many conserved cis-regulatory elements at the gene loci of LDTFs are often preferentially utilized for the induction of LDTF expression during Th cell differentiation and ILC development at different stages. In this review, we discuss the functions of lineage-related cis-regulatory elements in inducing T-bet, GATA3 or RORγt expression based on the genetic evidence provided in recent publications. We also review and compare the upstream signals involved in LDTF induction in Th cells and ILCs both in vitro and in vivo. Finally, we discuss the possible mechanisms and physiological importance of regulating LDTF dynamic expression during ILC development and activation.